Legal, Social and Cultural Prerequisites for the Development of ADR Forms in Lithuania and Ukraine - Nekrošius, Vytautas; Vėbraitė, Vigita; Izarova, Iryna; Prytyka, Yurii (Teisė, 2020)
Alternative Dispute Resolution (ADR) mechanisms include several procedures that allow parties to resolve their disputes out of court in a private forum, with the assistance of a qualified neutral intermediary of their choice. Arbitration and mediation are one of the most popular institutes of alternative dispute resolution. This article analyzes the legal, social, and cultural prerequisites for the development of the institutes of arbitration and mediation in Lithuania and Ukraine.
Keywords: arbitration; mediation; Alternative Dispute Resolution (ADR)